A prospective study on the natural course of low-grade squamous intraepithelial lesions and the presence of HPV16 E2-, E6- and E7-specific T-cell responses - Woo, Y.L.; van den Hende, M.; Sterling, J.C.; Coleman, N.; Crawford, R.A.F.; Kwappenberg, K.M.C.; Stanley, M.A.; Van Der Burg, S.H. (John Wiley & Sons, 2010)
This study investigates the clinical course of low grade squamous intraepithelial lesions (LSIL), HPV status and HPV16-specific immune response in a large prospective study of 125 women with LSIL followed cytologically, virologically and histologically. Women with low-grade abnormal smears were recruited and followed-up for one year. Colposcopy, cervical biopsy for histology and brushings for HPV typing was performed at recruitment, 6 months (no biopsy) and upon completion of the study at one year. HPV16-specific T-cell responses were analysed by interferon-γ ELISPOT at entry, 6 and 12 months. Infection with multiple HPV types was detected in 70% of all patients, HPV16 was found in 42% of the patients. LSIL lesions progressed to HSIL in 24%, persisted in 60% and regressed to normal in 16% of the patients. No difference was observed in the clearance rate of infections with single or multiple HPV types among the groups with a different histological outcome. HPV16-specific type 1 T-cell responses were detected in only half of the patients with an HPV16+ LSIL, and predominantly reactive to HPV16 E2 and E6. Interestingly, the presence of HPV16 E2-specific T-cell responses correlated with absence of progression of HPV16+ lesions (p = 0.005) while the detection of HPV16 E6 specific reactivity was associated with persistence (p = 0.05). This large prospective study showed that the majority of LSIL persisted or progressed within the first year.This was paralleled by immune failure as most of the patients with an HPV16+ LSIL failed to react to peptides of HPV16 E2, E6 or E7.